Surface damage in woven carbon composite panels under orthogonal and inclined high-velocity impacts - Marchante Rodriguez, Veronica; Grasso, Marzio; Zhao, Yifan; Liu, Haochen; Deng, Kailun; Roberts, Andrew; Appleby-Thomas, Gareth J. (MDPI, 2022)
The present research is aimed at the study of the failure analysis of composite panels impacted orthogonally at a high velocity and with an angle. Woven carbon-fibre panels with and without external Kevlar layers were impacted at different energy levels between 1.2 and 39.9 J. Sharp and smooth gravels with a mass from 3.1 to 6.7 g were used to investigate the effects of the mass and the contact area on the damage. Optical microscopy and thermography analyses were carried out to identify internal and surface damage. It was identified that sharp impactors created more damage on the impacted face of the panels, while the presence of a Kevlar layer increased the penetration limit and reduced the damage level in the panel at a higher energy.
Keywords: impact tests; gas gun; damage analysis; optical microscopy; thermography